The Effect of Canal Preparation with Four Different Rotary Systems on Formation of Dentinal Cracks: An In Vitro Evaluation - Khoshbin, Elham; Donyavi, Zakyeh; Abbasi Atibeh, Erfan; Roshanaei, Ghodratollah; Amani, Faranak (Iranian Endodontic Journal, 2018)
Introduction: Endodontic rotary systems may result in dentinal cracks. They may propagate to vertical root fracture that compromises the outcome of endodontic treatment. This study aimed to compare Neolix and Reciproc (single-file systems), Mtwo and ProTaper (conventional rotary systems) in terms of dentinal crack formation in root canal walls. Methods and Materials: This in vitro study was conducted on 110 extracted human single-rooted teeth. The teeth were randomly divided into four experimental groups (n=25) for root canal preparation with Neolix, Reciproc, Mtwo and ProTaper systems and two control groups (n=5). The first control group underwent root canal instrumentation with hand files while the second control group received no preparation and was only irrigated. After instrumentation, root canals were horizontally sectioned at 3, 6 and 9 mm from the apex and inspected under a stereomicroscope under 12× magnification for detection of cracks. The data were analyzed using chi-square, GEE test and Bonferroni tests (P<0.05). Results: No crack was found in the control groups. All rotary systems caused dentinal cracks. ProTaper, Reciproc, Mtwo and Neolix caused cracks in 92%, 80%, 68% and 48% of samples. ProTaper caused significantly more cracks than Neolix and Mtwo (P<0.05). No significant differences were noted between other groups (P>0.05). Conclusion: All rotary systems cause dentinal cracks and it is significantly different in apical, middle and coronal third of the root. Neolix appears to be a suitable alternative to other rotary systems since use of this single-file system saves time and cost and minimizes trauma to dentinal walls. Keywords: Dentinal Crack; Endodontics; Root Canal Preparation; Rotary System